A health-promoting role of exclusive breastfeeding on infants through restoring delivery mode-induced gut microbiota perturbations - Liu, Yu; Ma, Jingmei; Zhu, Baoli; Liu, Fei; Qin, Shengtang; Lv, Na; Feng, Ye; Wang, Shuxian; Yang, Huixia (Frontiers in Microbiology, 2023)
The establishment of human gut microbiota in early life is closely associated with both short- and long- term infant health. Delivery mode and feeding pattern are two important determinants on infant gut microbiota. In this longitudinal cohort study, we examined the interplay between the delivery mode and feeding pattern on dynamics of infant gut microbiota from 6 weeks to 6 months post-delivery in 139 infants. We also assessed the relationship between infant respiratory infection susceptibility and gut microbial changes associated with delivery mode and feeding pattern. At 6 weeks postpartum, the composition and structure of gut microbiota of cesarean section-delivered (CSD) infants differed from those of vaginally delivered (VD) infants, with decreased Bacteroides and Escherichia-Shigella and increased Klebsiella, Veillonella and Enterococcus. At 6 months postpartum, these delivery mode-induced microbial shifts were restored by exclusive breastfeeding, resulting in similar gut microbial profiles between VD and CSD infants who were exclusively breast fed (P=0.57) and more variable gut microbial profiles between VD and CSD infants who were mixed fed (P<0.001). We identified the VD-associated genera was enriched in healthy infants, while the CSD-associated genera enriched in infants suffered respiratory infections. Our findings suggest that exclusive breastfeeding may play a health-promoting role by reducing infant respiratory infection susceptibility through the restoration of gut microbiota perturbations caused by cesarean section